(3GdYdh ddYdj GdZaGQ aj EjVGM UMjM GdCNHGQ hSbjegGs - (3GdJQceGfj GdeUQj, GdPgHj, CHh YHO Gddg, TeS GdOjf, eMeO Hf CMeO Hf YKeGf Hf bGjeGR, J (B748(3g`s ((3eMeO Hf YHO Gddg GdLHQJjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdYdj GdYXje QH GdYQT GdYXje CeG HYO aEffj cfJ aj SfI EMOi hJSYjf hSJeGFI LeYJ CMGOjK hBKGQ aj eSCdI GdYdhs
(3BNQgG (B:s
(3hGVWQGH agdehG HfG Edi GdGJaGb Ydi GdJfRjg GdYGe hGdJhMjO GdJGe hGdEjeGf HeG LGA Yf Gddg hQShdg Ydi eG CQGO hGdca Yf GdcdGe hGdNUGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 326s
(3eYLe GdeDdajf (B3 / 80s
(3CYdGe GdfHdGA (B1 / 76s
(3TPQGJ GdPgH (B6 / 153s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds